1994
DOI: 10.1152/jn.1994.71.5.1646
|View full text |Cite
|
Sign up to set email alerts
|

The parabrachial area: electrophysiological evidence for an involvement in visceral nociceptive processes

Abstract: 1. Neurons (n = 142) were recorded with extracellular micropipettes in the parabrachial (PB) area, in the anesthetized rat, some of them being antidromically driven from the centralis nucleus of the amygdala (Ce). The spontaneous activity of these neurons was low, (10th percentile < median frequency < 90th percentile; 0.01 < 0.3 < 11 Hz), and the activity of a very high proportion of the PB neurons (89%, 127/142) were affected by mechanical or thermal cutaneous stimuli almost exclusively in the noxious range; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
123
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(146 citation statements)
references
References 0 publications
21
123
1
Order By: Relevance
“…CRD induced Fos expression in spinal neurons that project to the parabrachial area (Traub and Murphy 2002). A majority of PB neurons (66%) responded to visceral stimuli (intraperitoneal bradykinin and/or CRD) and almost all of them also had cutaneous receptive fields (Bernard et al 1994). These numbers match the findings of the present study, in which 62% of CeLC neurons responded to CRD and 98% also to somatosensory stimuli.…”
Section: Contribution Of Rossupporting
confidence: 89%
See 2 more Smart Citations
“…CRD induced Fos expression in spinal neurons that project to the parabrachial area (Traub and Murphy 2002). A majority of PB neurons (66%) responded to visceral stimuli (intraperitoneal bradykinin and/or CRD) and almost all of them also had cutaneous receptive fields (Bernard et al 1994). These numbers match the findings of the present study, in which 62% of CeLC neurons responded to CRD and 98% also to somatosensory stimuli.…”
Section: Contribution Of Rossupporting
confidence: 89%
“…Therefore the PB could serve as the major source of visceronociceptive input to the CeLC. However, the proportion of visceronociceptive CeLC neurons that were excited by CRD (87%) was larger than that of PB neurons (53%; Bernard et al 1994).…”
Section: Contribution Of Rosmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, in vivo single-unit recordings showed that the majority of CeA neurons also responded to noxious superficial (skin) and deep body (joint) mechanical and/or thermal stimuli [46,47] of a wide range of body parts. Most of these nociceptive neurons could be divided into two distinct populations: one group was excited (46%) and preferentially located in the CeC, whereas the other group was inhibited (34%) by noxious stimulation and mainly located in the center of the CeL [45]. In confirmation of these results, fMRI studies in humans have shown besides other brain areas, the activation of the amygdala in response to noxious stimulation [48].…”
Section: Spinopontoamygdaloid Pathwaymentioning
confidence: 55%
“…Initially, electrophysiological recordings in vivo found that the majority (70%) of pPB neurons projecting to the CeA, identified by antidromic stimulation, responded to either noxious mechanical and/or thermal stimulation [39] as well as to noxious visceral stimuli [45]. Most neurons had large receptive fields and were able to respond to stimulation of several parts of the body [39].…”
Section: Spinopontoamygdaloid Pathwaymentioning
confidence: 99%